Effect of hook design on longline catches in Lakshadweep Sea, India - Aneesh Kumar, K. V.; Khanolkar, Paresh S; Pravin, P; Madhu, V. R.; Meenakumari, B (Indian Journal of Fisheries, 2013)
Tuna longlining is considered as an ecofriendly, economical, species-selective and size-selective fishing technique suitable for harvesting sparsely distributed large predatory fishes. Many non-targeted and protected species like marine turtles, seabirds, cetaceans and sharks are also caught as bycatch in the pelagic longline gear. Investigations were undertaken to evaluate the effect of hook design on the longline catches in Lakshadweep Sea by comparing the species selection efficiency, bait holding efficiency and hooking pattern of the Japanese and circle hook designs. The results indicated that hook design has no effect on the catching efficiency, species selectivity and bait holding ability in pelagic longline fisheries in Lakshadweep Sea. The hooking pattern was found to be significantly different, indicating favorable hooking locations in the case of circle hooks. The results of the present study, indicated the positive effects of circle hooks in minimising the impact of bycatch by hooking on the fish favouring post-release survival of the species.